Burden of type 2 diabetes and its relationship with human development index in Asian countries: Global Burden of Disease Study in 2019 - Seyed Ahmadreza Alinaghian; Shokoufeh Hamidzadeh; Afsaneh Badrizadeh; Zaher Khazaei; Amirhossein Souri; Victoria Momenabadi; Elham Goodarzi (BMC Public Health)
Abstract Background The mounting burden of type 2 diabetes is a major concern in healthcare systems worldwide. The purpose of this study is to investigate Burden of type 2 diabetes and its relationship with human development index in Asian countries. Methods All accessible data from the 2019 Global Burden of Disease study were used to estimate the diabetes mellitus type 2 prevalence, mortality and disability-adjusted life years and diabetes mellitus type 2 in Asia from 1990 to 2019. We estimated all-cause and cause-specific mortality, years of life lost (YLLs), years lived with disability (YLDs), disability-adjusted life-years (DALYs) and attributable risk. Results The results indicated that the human development index (HID) was positively and significantly correlated with the incidence of type 2 diabetes in men (r = 0.481, P < 0.05) and women (r = 0.414, P < 0.05, but the correlation between death and the HDI was not significant in men and women (P > 0.05). The highest share of DALY risk factors in men (12093.2 per 100000) and in women (7122.4 per 100000) was related to behavioral factors. According to the results, air pollution, high fasting plasma glucose, and dietary risks are the main risk factors associated with the burden of type 2 diabetes in women and men, respectively. Conclusion Given that the burden of type 2 diabetes is escalating in Asia and the burden of disease can be largely controlled by managing its risk factors, the disease management program in different countries, especially in countries with high prevalence and high burden could be reduced by making policies.